G147(P) Sustained enhancement of team learning two years after implementing a simple initiative. (25th October 2020) - Coleman, H; Milne, S; Rae, V; Jarman, K; McQuaige, F; Bee, N; Joseph, S; Stark, M
Abstract : Background: We identified significant challenges to longitudinal team learning in the Acute Receiving Unit of our quaternary paediatric hospital. These included shift work, trainee rotation and a high service demand. We hypothesised that a regular 'Learning Points' email would be a simple and cost-free way to address this. Since establishing this departmental project in 2017 we have sought to improve and expand throughout the hospital. Aims: Our key aims were to: Inspire and enhance team work and learning – both within and between departments Promote evidence–based practice Promote a culture of quality improvement and patient safety, highlighting local and national initiatives. Methods: Regular emails were compiled by a small group of paediatric trainees. Content included interesting cases, clinical teaching, quality improvement and patient safety information. An initial electronic survey in January 2018 yielded positive feedback and identified areas to improve. Subsequently circulation was widened to include staff from other departments (consultants, senior nursing staff, paediatric ST1-8, GP and FY trainees). Contributions were invited from recipients. The email template was updated and changed to PDF form to enable e-portfolio use. A follow-up electronic survey was disseminated in July 2019 to re-evaluate our intervention. This included space for free-text comments. Questions included: Do you find the learning points email a useful learning resource? If so, can you explain what the key benefits of it are? Do you feel that reading the learning points email has influenced your practice? Would you recommend reading the learning points email to a colleague? Results: There were 26 respondents out of 111 (response rate 23%). 100% found the email a useful learning resource and 100% would recommend it to a colleague. 96% felt the emails had influenced their practice. 62% 'always' read the emails, 38% 'usually' and 0% 'never'. Themes identified amongst open question responses included: improved team spirit, practical knowledge, continuous professional development, quality improvement, patient safety, applicability, and use for trouble-shooting. Conclusion: This simple initiative demonstrates success and longevity in promoting a culture of team learning, quality improvement and patient safety in our hospital. Relatively low survey response rate is acknowledged as a limitation of our evaluation method.